Ultrafast and Stable Organic Single‐Crystal Vertical Phototransistor for Self‐Powered Photodetection and High‐Speed Imaging. (12th December 2022) - Zhang, Yuting; Qin, Shuchao; Du, Qianqian; Gan, Yuquan; Zhao, Jing; Li, Mengru; Zheng, Xialian; Wang, Anran; Liu, Yunlong; Li, Shuhong; Dong, Ruixin; Nie, Zhonghui; et al.
Abstract: Organic semiconductor crystals herald new opportunities for fabricating high‐performance optoelectronic devices, due to their intrinsic properties including outstanding charge transport properties, long exciton lifetime, and diffusion length. Despite remarkable progress in key figures of merit, the cut‐off frequency and responsivity are still lagging behind for most currently reported organic devices. Here, a high‐performance broadband vertical phototransistor based on rubrene single crystal, whose response covers the UV to visible range (300–650 nm) is reported. It shows a record‐high −3 dB bandwidth of ≈18 kHz and a maximum photoresponsivity of 10 5 A W −1 . Due to the asymmetric Schottky contact and excellent light absorption of organic crystal, the device exhibits excellent zero‐bias photoresponse even under ultralow light illumination (≈114 fW). In particular, such organic vertical phototransistor holds good air stability and environmental robustness, and even without any form of encapsulation, no degradation of performance is observed for 2 months continuous operating. In addition, several single‐pixel imaging to show its potential for practical applications are demonstrated. The results provide a promising strategy to fabricate ultrafast and sensitive organic photodetectors for future video‐frame‐rate imaging. Abstract : A high‐performance broadband vertical phototransistor based on rubrene single crystal, covering the UV to visible range (300–650 nm) is demonstrated. It shows a record‐high −3 dB bandwidth of ≈18 kHz and a maximum photoresponsivity of 10 5 A W −1 . In UV and visible range, high‐speed imaging was demonstrated, showing its potential for practical applications.